A cross-cultural study of co-design: the impact of power distance on group dynamics in Japan. Issue 1 (2nd January 2021) - Taoka, Yuki; Kagohashi, Kaho; Mougenot, Céline
ABSTRACT: This study explores the characteristics of collaboration between people with Japanese value orientation in co-design workshops. We define co-design as an approach where designers collaborate with non-designers to design new products or services. This research investigates the effect of culture and value orientation on co-design between designers and non-designers in a Japanese context. Through interviews with four professional designers, we identified that the participation of Japanese non-designers in a co-design workshop might be hindered by the presence of an expert, who is perceived as a person in a higher social position. With 20 subjects, we experimentally investigated the impact of power distance on collaboration. European and Japanese groups of non-designers generated and discussed ideas in two conditions – with or without a professional designer in the group. Through behaviour and speech analysis, we assessed the quality of collaboration within the group. Depending on their power distance score, the contributions of participants were affected differently by the presence of a professional designer. Unlike in the European groups, the presence of a designer in a Japanese group created a hierarchical structure that hindered the participation of non-designers. This work is expected to support the development of co-design methods adapted to their cultural contexts.